Awareness and use of the 11+ injury prevention program among coaches of adolescent female football teams. Issue 6 (December 2018) - Donaldson, Alex; Callaghan, Aisling; Bizzini, Mario; Jowett, Andrew; Keyzer, Patrick; Nicholson, Matthew
Coaches are essential to participant safety, particularly by implementing injury prevention programs. The evidence-based injury prevention programs developed by sports scientists will not prevent injuries in real-world sports settings if they are not properly implemented. This study investigated the knowledge and use of the highly efficacious 11+ injury prevention program among coaches of adolescent, female football teams, in Victoria, Australia. A cross-sectional online survey based on the RE-AIM framework identified that nearly half (42%) of the 64 respondents (response rate = 36%) were not aware of the 11+, and only one-third (31%) reported using it. Three-quarters (74%) of the 19 respondents who reported on the 11+ components they used, did not use the entire program. Nearly half (44%) of the 18 respondents who reported the frequency with which they used the 11+, used it less than the recommended twice a week. Barriers to implementing the 11+ included: limited awareness of the 11+; lack of knowledge about how to implement it; not having time to implement it; and believing that the 11+ does not incorporate appropriate progression. This study suggests that it is unlikely that the 11+ prevents a significant number of injuries in real-world football settings due to the lack of awareness and use among coaches. Football-governing bodies should use evidence-based strategies to raise awareness of the 11+, build coach competency to implement it, and address time-related implementation barriers that coaches experience. Coaches should keep up-to-date with injury prevention research evidence and prioritize injury prevention at training, including allocating time to implement injury prevention programs properly.